Inratemporal abscess : Management challenge and review on surgical approach - Salman, Amiruddin; Nor Kamaruzaman, Esa; Mohd Sayuti, Razali; Zul, Izzi; Amran, Mohamad (2017)
Infratemporal fossa abscess is a rare condition and difficult to be diagnosed clinically as the symptom is vague and mimicking trigeminal neuralgia without obvious facial swelling. Appropriate radiological imaging is very crucial to determine the focal infection. Drainage of the abscess is also challenging due to limited access. We are reporting a case of healthy middle age man who had multiple visit to dental clinic due to toothache and tooth extraction worsened the condition.